Towards a general "Europeanization" of EU Member States' energy policies? - Sebastian Strunz; Erik Gawel; Paul Lehmann (Helmholtz-Zentrum für Umweltforschung (UFZ), 2014)
It is often argued that energy policy is too fragmented across EU Member States and should be Europeanized to pave the way towards an efficiently organized European power system, which rest on the internal market for energy and a pan-European super-grid. However, this view neglects i) the factual heterogeneity of European energy policies in terms of harmonization and centralization, ii) economic arguments in favor of decentralization and iii) legal as well as political-economic obstacles against centralization of decision making. In this vain, we point out that a plea for a stronger role of the EU needs to be made with care and differentiation.
Keywords: 330; centralization; energy transition; EU climate and energy policy; fiscal federalism; harmonization; political economy